2023
DOI: 10.3390/ph16101379
|View full text |Cite
|
Sign up to set email alerts
|

Unlocking the Power of Onion Peel Extracts: Antimicrobial and Anti-Inflammatory Effects Improve Wound Healing through Repressing Notch-1/NLRP3/Caspase-1 Signaling

Rafik Mounir,
Walaa A. Alshareef,
Eman A. El Gebaly
et al.

Abstract: Onion peels are often discarded, representing an unlimited amount of food by-products; however, they are a valuable source of bioactive phenolics. Thus, we utilized UPLC-MS/MS to analyze the metabolomic profiles of red (RO) and yellow (YO) onion peel extracts. The cytotoxic (SRB assay), anti-inflammatory (Griess assay), and antimicrobial (sensitivity test, MIC, antibiofilm, and SP-SDS tests) properties were assessed in vitro. Additionally, histological analysis, immunohistochemistry, and ELISA tests were condu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 51 publications
2
3
0
Order By: Relevance
“…Similar MIC values were obtained in a study by Mounir et al (2023), which showed that yellow onion peel extract can limit skin infection with Candida albicans in vivo. [60].…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…Similar MIC values were obtained in a study by Mounir et al (2023), which showed that yellow onion peel extract can limit skin infection with Candida albicans in vivo. [60].…”
Section: Discussionsupporting
confidence: 84%
“…Candida albicans was sensitive to the action of all extracts, with MIC values ranging from 1.56 to 12.05 mg/mL. Similar MIC values were obtained in a study by Mounir et al (2023), which showed that yellow onion peel extract can limit skin infection with Candida albicans in vivo. [60].…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…Once the rats were sedated, their back hair was shaved, and their skin was purified using an alcohol solution and cleaned with sterile water. A circular wound with an approximate diameter of 10 mm was made using a skin biopsy tool and surgical scissors [ 43 ].…”
Section: Methodsmentioning
confidence: 99%
“…It displayed an effective biofilm inhibitory activity on the initial biofilm adherence and formation in addition to a little destructive effect on mature biofilm masses. 29 Pomegranate peel Pomegranate (Punica granatum L., Punicaceae) is one of the oldest cultivated fruits across the world. Its fruit juice processing industry generates a considerable quantity of waste fraction composed of the fruit residuals including the seed and the external peel.…”
Section: Agro-food Biowaste With Biofilm Inhibitory Effect Onion Peelmentioning
confidence: 99%